Comprehensive knowledge of reservoir hosts is Key to mitigate Future pandemics (2020)
COVID-19 and other epidemics (such as SARS, Ebola and H1N1) are stark reminders that knowledge of animal behavior and ecosystem health are key to controlling the spread of zoonotic diseases early in their onset. However, we have very limited information about the set of behavioral and ecological factors that promote viral spillover and the effects that has on ecosystem health and disease transmission. Thus, expanding our current knowledge of reservoir hosts and pandemics, represents an urgent and critical tool in ecological epidemiology. We also propose to create an integrative database that ranks animal species in terms of their likelihood as a host for specific infectious diseases. We call for a global and cooperative effort of field and laboratory scientists to create, maintain, and update this information in order to reduce the severity of future pandemics.